KNOWLEDGE AND APPLICATION OF THE SAFETY PROTOCOL FOR MEDICATION PRESCRIPTION AMONG MEDICAL STUDENTS - Bezerra, Isadora Rodrigues; Boeira, Elisângela Rodrigues; Alves, Clery Mariano da Silva (CIPEEX, 2025)
The study aimed to evaluate the knowledge and application of the Safety Protocol for the Prescription, Use, and Administration of Medications among clinical cycle and internship medical students at the Universidade Evangélica de Goiás. This is a cross-sectional observational study with a sample of 98 students. Data were collected through an online questionnaire and analyzed quantitatively. The results revealed that 82 (83.7%) of the participants know the protocol; however, of these, 43 (52.4%) do not apply it in their prescriptions. Most students include essential information in their prescriptions, but there are gaps in the correct completion of some data, such as the use of inappropriate abbreviations and the failure to include all mandatory information. It is concluded that, despite knowledge of the protocol, its practical application still faces significant challenges, such as a lack of guidance and support in clinical environments. The effective integration of this protocol into academic training is essential to improve patient safety, as highlighted by recent studies on the importance of medical education in preventing medication errors.